Epidermal cell tumors the basics - Smoller, Bruce R. (Springer, 2011)
Epidermal Cell Tumors: The Basics will serve as an effective and efficient handbook for the student of dermatopathology, and as a practical bench reference for the practicing diagnostician who desires rapid access to criteria that are useful in differentiating histologically similar entities. The reader will be able to focus upon a single histologic observation, i.e., inflammatory conditions without epidermal changes, and use this as a starting point from which to build a differential diagnosis based upon pattern recognition. As each entity is addressed, there will be a concise disorder.